A research handbook for patient and public involvement researchers - Bee, Penny; Brooks, Helen; Callaghan, Patrick; Lovell, Karina (Manchester University Press, 2018)
This handbook is written for patients and members of the public who want to understand more about the approaches, methods and language used by health-services researchers. Patient and public involvement (PPI) in research is now a requirement of most major health-research programmes, and this book is designed to equip these individuals with the knowledge and skills necessary for meaningful participation. Edited by award-winning mental-health researchers, the book has been produced in partnership with mental-health-service users and carers with experience of research involvement. It includes personal reflections from these individuals alongside detailed information on quantitative, qualitative and health-economics research methods, and comprehensively covers all the basics needed for large-scale health research projects: systematic reviews; research design and analysis using both qualitative and quantitative approaches; health economics; research ethics; impact and dissemination. This book was developed during a five-year research programme funded by the UK's National Institute for Health Research (NIHR) called Enhancing the Quality of User Involved Care Planning in Mental Health Services (EQUIP). The handbook clearly outlines research practices, and gives an insight into how public and patient representatives can be involved in them and shape decisions. Each chapter ends with a reflective exercise, and there are also some suggested sources of additional reading. People who get involved in health research as experts from experience now have a textbook to support their research involvement journey.